Common genetic variants in the FETUB locus, genetically predicted fetuin-B levels, and risk of insulin resistance in obese Chinese adults. Issue 50 (December 2017) - Li, Zhibin; Liu, Changqin; Shi, Xiulin; Chen, Zheng; Wang, Dongmei; Li, Long; Tu, Yichang; Lin, Mingzhu; Liu, Suhuan; Yang, Shuyu; Li, Xuejun
Abstract : Abstract: Elevated serum fetuin-B is suggested to be associated with insulin resistance, but it is unknown if this association is causal. The aim of this study was to explore the potential causal relationship between fetuin-B and insulin resistance. We used Mendelian randomization analysis by incorporating information of genetic variants in FETUB and serum fetuin-B concentrations with insulin resistance in 1148 obese Chinese adults. Common genetic variants ( FETUB rs4686434, rs6785067, and rs3733159) were significantly associated with serum fetuin-B concentrations but not with insulin resistance. Higher serum fetuin-B levels were significantly associated with increased homeostasis model assessment of insulin resistance (HOMA-IR) (0.17 [95%CI: 0.01 to 0.32, P = .037] 10 −6 mol IU L −2 higher per SD). However, Mendelian randomization analysis using 3 single-nucleotide polymorphisms as instrumental variables did not support a significant association between genetically predicted fetuin-B levels and HOMA-IR (−0.09 [95%CI: −0.62 to 0.44, P = .738] 10 −6 mol IU L −2 lower per SD). The regression coefficients for measured and genetically predicted fetuin-B concentrations on HOMA-IR were significantly different ( P <.001). This study suggests the association between fetuin-B and insulin resistance may not be causal. Future studies on the nongenetic determinants of serum fetuin-B concentration to assess if such unmeasured factors may confound the association between fetuin-B and insulin resistance as well as more pathway analysis for this association are warranted.